Voters’ Motivation for Selecting the Party Leader: The Case of the Italian Democratic Party - Rombi, Stefano (Frontiers in Political Science, 2021)
Political parties suffer from a lasting, consolidated and, probably, irreversible crisis. However, they have begun a laborious process of adaptation which, among other things, has led to the spread of some new organizational practices. In general terms, looking at the party on the ground, we have seen a significant spread of inclusive procedures in party decision-making, which, in other words, has meant a strengthening of intra-party democracy. In particular, the inclusion of party members and, sometimes, sympathizers concerns not only the formulation of a policy position, but also the selection of party candidates and leadership. This article focuses on the inclusive process of leadership selection of the Italian Democratic Party (DP) occurred in 2013, 2017 and 2019. Since its inception, the Democratic Party has introduced the figure of the supporter, i.e. a voter not formally enrolled in the party but authorized to participate in a number of internal decision-making processes, including the selection of the party leader. Using the survey data from the research group Candidate and Leader Selection (CLS), the article explores the relationship between selectors and the primaries, looking particularly to the motivations behind the choice of vote. The analysis is based on over 8,000 interviews conducted through the exit poll technique and collected from 2013 to 2019. The article shows that voters self-positioning on the left-right axis and their strategic orientation are, in all three cases of primaries, the most relevant variables for explaining the selectors’ motivations.